The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpls.2020.542153
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Variation in Pea for Resistance Against a Root Rot Complex and Its Characterization by Amplicon Sequencing

Abstract: Wille et al.Pea Root Rot Resistance Screening offers a tool for selection at the seedling stage in breeding nurseries. Using the complexity of the infested field soil, the screening system provides opportunities to study plant resistance in the light of diverse plant-microbe interactions occurring in the rhizosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 79 publications
(89 reference statements)
1
17
0
Order By: Relevance
“…Similarly, it has been shown that arbuscular mycorrhizal fungi (AMF) increase the resistance of pea against Aphanomyces root rot (Thygesen et al, 2004). Recently, both microbial taxa were found within a diverse fungal community that included several known pea pathogens (Wille et al, 2020). In line with that, the study of Xu et al (2012a) has previously shown that the health status of pea is mainly related to the fungal community present in diseased roots but barely reflected by the fungal community in the soil.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Similarly, it has been shown that arbuscular mycorrhizal fungi (AMF) increase the resistance of pea against Aphanomyces root rot (Thygesen et al, 2004). Recently, both microbial taxa were found within a diverse fungal community that included several known pea pathogens (Wille et al, 2020). In line with that, the study of Xu et al (2012a) has previously shown that the health status of pea is mainly related to the fungal community present in diseased roots but barely reflected by the fungal community in the soil.…”
Section: Introductionmentioning
confidence: 76%
“…The experiment involved eight peas (P. sativum L.) genotypes that were selected based on a previous study on root rot resistance. These genotypes showed contrasting levels of resistance to a PRRC present in naturally infested field soil (Kirchlindach) (Wille et al, 2020). The present selection includes four varieties and four genebank accessions from the USDA-ARS GRIN Pea Core Collection (Supplementary Table 1).…”
Section: Plant Growth and Phenotypingmentioning
confidence: 99%
See 3 more Smart Citations